Alcohol consumption and risk of type 2 diabetes mellitus among males in The Manggis Area, Karangasem, Bali - I Gusti Ayu Mirah Adhi; Ni Luh Putu Suariyani; I Wayan Weta; Anak Agung Sagung Sawitri (Universitas Udayana, 2018)
Background and purpose: Diabetes mellitus (DM) is a serious health problem worldwide. Local alcohol consumption is one of Balinese’s traditions considered to be associated with the high incidence of DM. This study aims to determine the pattern of alcohol consumption and risk of type 2 DM in Manggis Subdistrict, Karangasem, Bali. Methods: A case control study was conducted in 55 men with type 2 DM as cases and 55 non-diabetic men as controls. Non-diabetic men were defined with fasting glucose level (GDP) <100 mg/dl and without clinical symptoms of DM. Cases were recruited from the patient’s register at the public health centre (PHC) in Manggis Sub-District and controls were recruited from similar neighborhood with the cases and matched by age. Data were collected over May-July 2017 by households’ interview using structured questionnaires. Multivariate analysis was employed using logistic regression to identify the risk factors of type 2 DM. Results: The characteristics of cases and controls were similar in terms of age, education and physical activity, but there was a significant difference in employment. Multivariate analysis showed that heavy alcohol consumption (AOR=7.84; 95%CI: 1.46-42.28), frequent consumption of high sugar alcohol drinks (AOR=3.45; 95% CI: 1.16-10.22), history of obesity (AOR=8.82; 95% CI: 2.43-32.01), employed (AOR=5.98; 95%CI: 1.89-18.93) and frequent consumption of sweetened beverages (AOR=39,57; 95%CI: 4.00-391,8) were significantly associated with the incidence of type 2 DM. No significant association was found between the duration of alcohol consumption and the incidence of type 2 DM. Conclusions: Alcohol consumption, a history of obesity, consumption of high sugar alcohol drinks, retirement/unemployment and consumption of sweetened beverages are associated with the incidence of type 2 DM. Education regarding those risk factors should be enhanced to reduce the incidence of type 2 DM.